Upcycling food waste digestate for energy and heavy metal remediation applications - Haili Chen (Resources, Conservation & Recycling: X, 2019)
Anaerobic digestate originating from food waste has been studied herein for two different purposes. Firstly, for combustion, co-granulation of the digestate and medium density fibreboard (MDF) dust with the addition of sodium silicate as the binder was used to produce the granular solid biofuel. It was found that increasing the content of the medium density fibreboard dust could increase the calorific value but had no significant effect on the strength of the final granules. Additionally, a significant reduction of the ash content was also observed. For heavy metal removal, granules made using the digestate and sodium silicate binder were carbonised to produce biochar which was characterised and applied as adsorbent materials. The biochar has a good removal capacity for both lead and cadmium, and the binder concentration had a positive correlation with the removal capacity of the resultant biochar. The maximum lead removal capacity (355.3 mg g−1) of biochar made using 3 wt.% sodium silicate binder, was six times more than the analogous commercial activated carbon. Langmuir model showed better fitting for adsorption data of Pb2+, while the Freundlich model showed better fitting of Cd2+. For both Pb2+ and Cd2+ kinetic data, the pseudo-second-order had a better correlation. Our approach helps aid and facilitate the concept of the circular economy by effectively up-cycling and valorising waste lignocellulosic biomass such as food waste digestate into value-added products.